Antihypertensive Effect of Rice Bran Derived Amino Acids Through Modulation of iNOS Expression and Renal Histopathology in DOCA Salt Induced Hypertensive Rats - Muhammad Fikri Nur; Devi Ramadani; Muh Fikry Baharuddin; Almas Dwi Khairana; Saidun Fiddaroini; Akhmad Sabarudin; Anna Safitri; Wibi Riawan; Dyah Kinasih Wuragil; Hilman Nurmahdi; Aulanni'am Aulanni'am (Jurnal Penelitian Pendidikan IPA, 2026)
Hypertension is a major global health concern and a leading risk factor for cardiovascular mortality. Conventional treatment with ACE inhibitors like captopril is effective but often causes adverse effects including cough, dizziness, and renal impairment. This study evaluated the antihypertensive effects of rice bran in DOCA-salt-induced hypertensive rats. In vitro analysis revealed 45.58% soluble fiber and rich amino acid content, including 2.121 mg L-Arginine, a nitric oxide precursor promoting vasodilation. Male Wistar rats were divided into five groups: negative control, positive control, captopril treatment (5 mg/kg BW), and rice bran supplementation at 1% and 2% of 25 g feed. The 2% rice bran group significantly (p < 0.05) reduced renal iNOS expression by 88.32% compared to hypertensive controls, surpassing captopril's 22.96% reduction. Histopathological examination revealed notable renal protection with complete absence of fatty degeneration and minimal glomerular inflammation in the 2% rice bran group. These findings demonstrate potent antihypertensive activity through ACE inhibition, enhanced nitric oxide bioavailability, and mitigation of oxidative and inflammatory stress, establishing rice bran as a promising natural therapeutic alternative for hypertension management